J.G. Fichte: método y praxis en su Wissenschaftslehre de Jena (1794-1799) - Corsico, Luciano (2014)
In this paper, I study Fichte’s method as a method of “transcendental deduction”, which has a strong relationship with the practical significance of his philosophy. Indeed, Fichte explicitly refers to his own method as a “deduction” (Deduction) in his writings Jena´s period (1794-1799). Although this deductive method is originally inspired by the Kantian philosophy, acquires a broader development in the system of WL, as a process of foundation on necessary principles of all human knowledge (theoretical and practical). In my point of view, Fichte’s transcendental deduction is a complex method, in which three elements are articulated: argumentation, intellectual intuition and reflection. I will argue that each of these methodological dimensions necessarily and permanently refers not only to the constitutive activity of consciousness, but also to praxis and its normative principles, originated from human reason.